CoCr porous scaffolds manufactured via selective laser melting in orthopedics: Topographical, mechanical, and biological characterization. Issue 7 (28th January 2019) - Caravaggi, Paolo; Liverani, Erica; Leardini, Alberto; Fortunato, Alessandro; Belvedere, Claudio; Baruffaldi, Fabio; Fini, Milena; Parrilli, Annapaola; Mattioli‐Belmonte, Monica; Tomesani, Luca; Pagani, Stefania
Abstract: Over the last decade, advances in additive manufacturing have allowed to obtain complex 3D porous lattice in materials suitable for orthopedic applications. Whereas 3D‐melted titanium alloys have been extensively investigated, little is the current knowledge on the feasibility of bone‐replicating CoCr porous scaffolds manufactured via selective laser melting (SLM). Moreover, the effect of topography on bone cells viability and proliferation has not been fully explored yet. Small cylindrical porous lattices were modeled from micro‐CT images of human trabecular bone, and from the repetition of spherical‐hollow and body‐centered cubic unit cells, and manufactured via SLM from CoCr powder. Macro‐ and microcharacterization of the porous samples were assessed using optical microscope, micro‐CT, and SEM. The scaffolds mechanical properties, measured via ISO testing, compared well with those of the human bone. Osteoblast‐like cells proliferation and viability were assessed in vitro, and compared to those cultured on a standard nonporous implant‐to‐bone interface, showing steady increase on all geometries over time. SEM analysis confirmed the quality of cells morphology, spread, and organization on all lattices. The SLM process appeared not to alter the biocompatibility of CoCr; however, 15–100 μm irregularities and macroalterations were observed in the porous scaffolds with respect to the 3D nominal models. © 2019 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater 107B: 2343–2353, 2019.